2014
DOI: 10.17741/bgsf/86.2.003
|View full text |Cite
|
Sign up to set email alerts
|

Svecofennian intra-orogenic gabbroic magmatism: A case study from Turku, southwestern Finland

Abstract: Svecofennian intra-orogenic gabbroic magmatism: a case study from Turku, southwestern Finland Using single-grain zircon U-Pb dating by LA-MC-ICPMS and whole-rock geochemistry, we have studied the Palaeoproterozoic gabbroic rocks from Moisio in southwest Finland. Three ages were obtained. The interpreted intrusion age is ~1.86 Ga, which places it in the 1.87-1.84 Ga intra-orogenic period of southern Svecofennia. The other ages, ~1.89 Ga and ~1.83 Ga, are inferred to be inherited and metamorphic ages, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…This suggests that the low-pressure anatexis in the study area can be related to mafic underplating in the lower crust, which dominated around 1.86 Ga and at 1.84-1.81 Ga at an early stage of each magmatic event, consistent with the ideas presented earlier in Andersson et al (2004) and Andersen et al (2009). The concept of intraorogenic mafic intrusions at deeper crustal level as a cause of high heat flow and crustal melting under low-P metamorphic conditions has also been envisaged in southern Finland by, for example, Schreurs and Westra (1985), Korja et al (1993), Korsman et al (1999), Väisänen et al (2000) and Nevalainen et al (2014). Furthermore, a magmatic source for the heat needed to produce at least the 1.87-1.86 Ga migmatites in the Ljusdal lithotectonic unit to the north, where voluminous magmatic activity at 1.86-1.84 Ga is present, has been proposed .…”
Section: Mechanism For Low-pressure Anatexis -Heat Transfer Related Tsupporting
confidence: 86%
“…This suggests that the low-pressure anatexis in the study area can be related to mafic underplating in the lower crust, which dominated around 1.86 Ga and at 1.84-1.81 Ga at an early stage of each magmatic event, consistent with the ideas presented earlier in Andersson et al (2004) and Andersen et al (2009). The concept of intraorogenic mafic intrusions at deeper crustal level as a cause of high heat flow and crustal melting under low-P metamorphic conditions has also been envisaged in southern Finland by, for example, Schreurs and Westra (1985), Korja et al (1993), Korsman et al (1999), Väisänen et al (2000) and Nevalainen et al (2014). Furthermore, a magmatic source for the heat needed to produce at least the 1.87-1.86 Ga migmatites in the Ljusdal lithotectonic unit to the north, where voluminous magmatic activity at 1.86-1.84 Ga is present, has been proposed .…”
Section: Mechanism For Low-pressure Anatexis -Heat Transfer Related Tsupporting
confidence: 86%
“…Firstly, rutile-and garnet-bearing pyroxenites are the likely source for the elevated Nb, Nb/Ta and OIB-like geochemical features in the HNB. The previously described ~1.86 Ga mafic intrusions from southern Finland (Väisänen et al, 2012a(Väisänen et al, , 2012bNevalainen et al, 2014) seem to share the same features. Moreover, the high Nb/Ta in the ~1.86 Ga HNB magmas seem to balance the low Nb/Ta observed in ~1.88 Ga arc rocks elsewhere in southern Finland (Fig.…”
Section: Formation Delamination and Partial Melting Of Arclogites Dur...supporting
confidence: 61%
“…Secondly, it explains the genetic link between the HNB, HMG and adakite-like rocks. Nevalainen et al (2014) observed more primitive gabbros associated with enriched monzogabbros, whereas Väisänen et al (2012b) described TTG-and adakite-like magmas associated with enriched diorites. These enriched monzogabbros and diorites are similar to HNB, which is a strong indication that identical processes were ongoing simultaneously in southern Finland.…”
Section: Formation Delamination and Partial Melting Of Arclogites Dur...mentioning
confidence: 98%
See 1 more Smart Citation
“…In southern Finland, recent research has revealed a phase of bimodal magmatism following shortly after, but clearly separate, from the dominant synorogenic magmatism in that area, including the 1865 ± 9 Ma Rauma diorite and the ca 1850 Ma Korpo diorite and granite (Väisänen et al 2012a), the 1860 ± 5 Ma Moisio gabbro (Nevalainen et al 2014), and ca. 1.86 Ga post-kinematic mafic dykes (Kara et al 2016).…”
Section: The Hedesunda I and Ii Granitoids Seen In A Wider Regional C...mentioning
confidence: 99%